Association between pulmonary embolism and seasonal meteorological parameters - Uslu, Muhammed Fuad; Yilmaz, Mustafa; Gümüştoka, Serdar (My University, 2025)
Aim: This study aimed to investigate the relationship between acute pulmonary embolism diagnoses and three meteorological parameters—average daily temperature, relative humidity, and atmospheric pressure—on the day of diagnosis. Materials and Methods: In this retrospective study, patients diagnosed with acute pulmonary embolism via radiological imaging  between January 1, 2019, and December 31, 2023 , were included. Data were collected from two hospitals in our province following approval from the local university ethics committee.  Patient information was extracted from electronic health records and digitized. Adults aged 18 years and older who presented within the study period  were eligible. For each case, the date (day, month, year, and season) of diagnosis was recorded . The relationship between these temporal data points and meteorological parameters was analyzed. Results: A total of 1,826 patients diagnosed with pulmonary embolism between 2019 and 2023 were included in the study. Although the highest number of monthly admissions occurred in January (8.54%), there was no statistically significant difference in admission rates across the months (p=0.56). Additionally, no significant correlation was found between the number of acute pulmonary embolism diagnoses and daily meteorological parameters. Conclusion: This study found no association between the incidence of acute pulmonary embolism and daily mean temperature, relative humidity, or atmospheric pressure.
Keywords: Environmental factors; seasonal variation; Meteorological parameters; acute pulmonary embolism; daily mean atmospheric pressure